Los derechos fundamentales en el ciberespacio - Núñez Robinson, Rodolfo (2025)
Fundamental rights must evolve to address the challenges of the contemporary digital environment. Building on the constitutional recognition of unenumerated rights, this work supports the existence of a fourth generation of human rights, centred on interconnectivity and the inherent risks and threats of cyberspace. Cybersecurity is presented not merely as a technical issue, but as a structural condition for the effective exercise of both traditional and emerging fundamental rights. This paper examines cyber threats and risks, emphasizing the need for a comprehensive risk management approach to safeguard individuals and their digital environment. It then identifies new fundamental digital rights: digital existence, digital identity, digital honour and reputation, digital freedom and responsibility, privacy, anonymity, the right to be forgotten, digital domicile, and the right to peace in cyberspace. Each is analysed from a constitutional, technical, and social perspective, highlighting its core content and the corresponding duties of both the State and private actors. The article concludes that in a hyperconnected society, the law cannot remain static. Protecting human dignity requires adapting the constitutional framework to the digital environment, recognizing and guaranteeing fourth-generation rights as essential tools to preserve individual freedom, autonomy, and well-being in cyberspace.